2021
DOI: 10.3389/froh.2021.675288
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of GILZ and SGK-1 in Potentially Malignant and Malignant Human Oral Lesions

Abstract: Glucocorticoid-induced leucine zipper and serum-glucocorticoid-regulated kinase-1 (SGK-1) are major glucocorticoid-inducible proteins. Recent studies indicate the local production of cortisol in oral mucosa, which can impact the tissue generation of glucocorticoid-induced leucine zipper (GILZ) and SGK-1. Furthermore, GILZ and SGK-1 play pathogenic roles in a variety of cancers, but their status in potentially malignant (e.g., epithelial dysplasia) or malignant oral lesions remains unknown. This study tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…A study has revealed that depression inhibits natural killer cells and DNA repair enzymes, which are essential for defense mechanisms against cancer [66]. Furthermore, cortisol secretion is increased in patients with depression, and local cortisol production in the oral mucosa upregulates serum glucocorticoid-regulated kinase-1 (SGK-1) expression [67,68]. SGK-1 activation and expression can favor the invasiveness and metastasis of human tumors, including tongue cancer [69].…”
Section: Discussionmentioning
confidence: 99%
“…A study has revealed that depression inhibits natural killer cells and DNA repair enzymes, which are essential for defense mechanisms against cancer [66]. Furthermore, cortisol secretion is increased in patients with depression, and local cortisol production in the oral mucosa upregulates serum glucocorticoid-regulated kinase-1 (SGK-1) expression [67,68]. SGK-1 activation and expression can favor the invasiveness and metastasis of human tumors, including tongue cancer [69].…”
Section: Discussionmentioning
confidence: 99%
“…For example, following serum stimulation, SGK-1 enters the nucleus while it is found in the cytosol in response to glucocorticoids or hypertonic shock. It is also found in mitochondria likely regulating cellular energy metabolism and autophagy and is associated with plasma membrane in both non-malignant and malignant oral lesions (Cordas et al, 2007;O'Keeffe et al, 2013;Zhu et al, 2020;Zhou et al, 2019;Mozaffari and Abdelsayed, 2021). Collectively, these observations indicate the complex and multifaceted role of SGK-1 in physiological processes and pathological conditions.…”
Section: Introductionmentioning
confidence: 85%
“…Aside from the use of glucocorticoids for a variety of noncancer disorders, they are also used for treatment of lymphohematopoietic neoplasms and as adjuvant therapy in non-hematological malignancies in order to limit adverse effects of chemotherapy and/or radiotherapy (7). Importantly, the following aspects are of relevance in relation to glucocorticoids and HPV-OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with intense interest in unraveling of the immune infiltrative landscape of HPV-positive vs. -negative head and neck tumors which, in turn, would help to better understand more favorable clinical outcome of HPVpositive than -negative squamous cell carcinoma and also strengthen the rationale for immunotherapy modalities (10-12). Third, glucocorticoids can affect the outcome of epithelial tumors via a number of mechanisms including impaired immune surveillance, anti-apoptotic effects, increased tumor cell energy metabolism and promoting chemotherapy resistance (7). Fourth, glucocorticoids regulate expression of several proteins which, aside from regulating immune and anti-inflammatory responses of glucocorticoids, they are implicated in etiopathogenesis of various cancers; these include the glucocorticoid-induced leucine zipper (GILZ), serum glucocorticoid-regulated kinase-1 (SGK-1) and Annexin-A1 (ANXA1) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation